Orbital and Ocular Adnexal Manifestations of Adult T-Cell Leukemia/Lymphoma: a Case Report and Systematic Review. Issue 3 (May 2021) - Henry, Roger K.; Bagg, Adam; Wu, Connie; Eagle, Ralph C.; Milman, Tatyana
Abstract : Purpose: To describe a patient with orbital adult T-cell leukemia/lymphoma (ATLL) and to review the literature on presentation, diagnostics, management, and clinical course of this rare disease. Methods: A systematic literature review. PubMed/MEDLINE and Google Scholar databases were searched for all well-documented cases of orbital/ocular adnexal ATLL. Results: Sixteen patients were included in the final analysis. The median age at diagnosis was 47 years (range, 20–85), 9/16 patients (56%) were male, and patients were of Japanese (10/16, 63%), Caribbean (5/16, 31%), or African (1/16, 6%) origin. Proptosis (6/15, 40%) and visual loss (5/15, 33%) were the most common presenting signs. Involvement of adjacent structures was documented in 8 of 16 (50%) patients. All patients had evidence of systemic ATLL, which was identified concurrently with orbital/ocular adnexal disease in 9 of 15 (60%) patients. Management included multi-agent chemotherapy with steroids (9/13, 69%), antivirals (2/13, 15%), biologic agents (4/13, 31%), and umbilical cord blood transplantation (1/13, 8%). Most patients (8/12, 67%) experienced at least partial remission with disease relapse occurring in 6 of 8 patients (75%). The median survival time was 28 months (95% CI, 5.5–50.5 months). Conclusions: Adult T-cell leukemia/lymphoma should be considered in the differential diagnosis of orbital and ocular adnexal space-occupying lesions, particularly in male patients from endemic regions. Orbital disease is frequently locally aggressive and presents concurrently with systemic ATLL, highlighting the importance of comprehensive multimodal work-up and multidisciplinary management. Emerging targeted therapies and hematopoietic stem cell transplant may prolong survival. Abstract : Orbital and ocular adnexal adult T-cell leukemia/lymphoma presents with orbital mass-effect or conjunctival lesions and systemic involvement in endemic populations and confers a 28-month median-survival-time, with targeted biologics and stem-cell transplantation providing new treatment options.Supplemental Digital Content is available in the text.